The prevalence of salmonella in milkfish obtained from five different sources. - Manlapig, Edith T. (College of Fisheries, University of the Philippines in the Visayas, 1981)
Salmonella are widely distributed in nature and may be transmitted to man via animals and animal by-products. Fish in the ponds are likely to be contaminated by these organisms when fed with infected feeding stuff. Organic fertilizers are also possible. The prevalence samples for salmonella was conducted on milkfish taken from different fishponds and wet markets. The test was carries by resuscitating first the 25 gram samples and then the rinse of the 30 samples. Positive samples for presumptive salmonella were taken from ponds using organic fertilizers (Pangasiinana, 20%), from trial B of fishpens (Los Banos, 10%), from trials A and B of fishponds were effluents drain (Bulavan, 10% and 13% respectively. Negative results were obtained from the ponds surrounded by thickly populated area (Malabon), and from the twowet markets (divisoria and quipap). Negative result was likewise obtained from the frozen intestines of samples that gave results with the rinse technique. The average TPC of the samples taken from Pangasinan was 1.00x105 organism per gram. It was found out that salmonella couldn be detected in ponds using organic fertilizers, especially chicken manure and contaminated feeding stuff.